2017
DOI: 10.1007/s00115-017-0370-7
|View full text |Cite
|
Sign up to set email alerts
|

Netzwerke für motorische Kognition

Abstract: Apraxia is an umbrella term for different disorders of higher motor abilities that are not explained by elementary sensorimotor deficits (e. g. paresis or ataxia). Characteristic features of apraxia that are easy to recognize in clinical practice are difficulties in pantomimed or actual use of tools as well as in imitation of meaningless gestures. Apraxia is bilateral, explaining the cognitive motor disorders and occurs frequently (but not exclusively) after left hemispheric lesions, as well as in neurodegener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…From a motor systems perspective, our data provide in vivo evidence for a particular involvement of higher motor regions in the spreading of tau pathology with symptomatic disease progression, which is a novel finding. Lesion studies, mainly performed in stroke patients, indicate that cognitive-motor processes are organized in dorso-dorsal, ventro-dorsal, and ventral processing streams ( Martin et al, 2017 ). Our results suggest that particular the dorso-dorsal stream (e.g., dorsal premotor cortex, superior parietal cortex) and part of the ventro-dorsal processing stream (e.g., angular gyrus) are affected by tau pathology in AD.…”
Section: Discussionmentioning
confidence: 99%
“…From a motor systems perspective, our data provide in vivo evidence for a particular involvement of higher motor regions in the spreading of tau pathology with symptomatic disease progression, which is a novel finding. Lesion studies, mainly performed in stroke patients, indicate that cognitive-motor processes are organized in dorso-dorsal, ventro-dorsal, and ventral processing streams ( Martin et al, 2017 ). Our results suggest that particular the dorso-dorsal stream (e.g., dorsal premotor cortex, superior parietal cortex) and part of the ventro-dorsal processing stream (e.g., angular gyrus) are affected by tau pathology in AD.…”
Section: Discussionmentioning
confidence: 99%
“…The supramarginal cortex has been assigned to the ventro-dorsal processing stream/praxis network, which has been discussed to process action knowledge required for a proper tool/object manipulation (Kleineberg et al, 2018). The angular gyrus itself is considered to be relevant even for more than one praxis processing streams (Martin et al, 2017c). Additionally, posterior middle temporal gyrus/ middle occipital gyrus are part of the praxis network (Martin et al, 2017a) and do partially overlap with the clusters identified in the temporal and occipital regions here.…”
Section: Discussionmentioning
confidence: 99%
“…The angular gyrus itself is considered to be relevant even for more than one praxis processing streams (Martin et al, 2017c). Additionally, posterior middle temporal gyrus/ middle occipital gyrus are part of the praxis network (Martin et al, 2017a) and do partially overlap with the clusters identified in the temporal and occipital regions here. Thus, a causal link between tau-induced neuronal dysfunction in these regions and observed apraxia symptoms appears in fact possible.…”
Section: Discussionmentioning
confidence: 99%
“…Since the study primarily focused on (disturbed) connectivity in apraxia, our analysis focused on basic and complex motor systems. Based on previous research on the neuroanatomical and functional organization of the praxis networks and their pathophysiology (i.e., networks involved in apraxia; Martin et al, 2017; Schmidt & Weiss, 2021), as well as sensory and cognitive processing networks mentioned previously (Smith et al, 2009), we selected 10 intrinsic connectivity networks (ICNs), namely: (i) left primary sensorimotor cortex; (ii) right primary sensorimotor cortex; (iii) bilateral supplementary motor area (SMA); bilateral premotor cortex (PMC); (v) left cerebellum; (vi) right cerebellum; (vii) bilateral intraparietal sulcus (IPS); (viii) bilateral inferior parietal lobule (IPL); (ix) left fronto-parietal network; (x) right fronto-parietal network. As our motor and apraxia assessment are based on verbal commands and visual representations, we additionally included a visual and auditory ICN.…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous research on the neuroanatomical and functional organization of the praxis networks and their pathophysiology (i.e., networks involved in apraxia; Martin et al, 2017;Schmidt & Weiss, 2021), as well as sensory and cognitive processing networks mentioned previously (Smith et al, 2009), we selected 10 intrinsic connectivity networks (ICNs), namely: (i) left primary sensorimotor cortex; (ii) right primary sensorimotor cortex; (iii) bilateral supplementary motor area (SMA);…”
Section: Static and Dynamic Connectivitymentioning
confidence: 99%